1958
DOI: 10.1172/jci103684
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between a Range of Tissue Temperature and Local Oxygen Uptake in the Human Forearm. I. Changes Observed Under Resting Conditions12

Abstract: The advent of the use of hypothermia as an adjunct to surgery has revived interest in the effect of alterations of local temperature on tissue metabolism. In the early part of this century, several investigators (1, 2) performed in v4tro studies and found that increasing the temperature of muscle slices raised their oxygen consumption, while an opposite effect was produced by decreasing the temperature. The Q10 of this relationship was generally found to be slightly above the value of two (2). However, one lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…were approximately the same as the figures reported in previous papers (4,5). The difference observed between the average resting oxygen uptake at a bath temperature of 45°and that at 28 to 300 (Table I) was found to be statistically significant, with a p < 0.01 (8).…”
Section: Resultssupporting
confidence: 88%
“…were approximately the same as the figures reported in previous papers (4,5). The difference observed between the average resting oxygen uptake at a bath temperature of 45°and that at 28 to 300 (Table I) was found to be statistically significant, with a p < 0.01 (8).…”
Section: Resultssupporting
confidence: 88%
“…No significant differences were observed between the data. This is in contrast with measurements obtained on the forearm at rest were a Q 10 of 2-2.5 was found for O • 2 (Abramson et al, 1957;Abramson et al, 1958;Binzoni et al, 1999;Binzoni et al, 2001). A possible explanation of this discrepancy, is that in Koga et al (1997) (Janssen et al, 2000).…”
Section: Oxygen Consumption At Restmentioning
confidence: 72%
“…One of the first measurements of human muscle O • 2 at rest ("forearm") as a function of local T were performed by Abramson et al (1957) ("forearm") immediately after 5 minutes arterial occlusion, compared to the control condition with no arterial occlusion. The increase of O…”
Section: Oxygen Consumption At Restmentioning
confidence: 99%
“…Thus, the data of several authors, 16 ' 18 who found clear changes in muscle blood flow over the entire physiological temperature range, might be explained by specific opening of shunts due to increase in temperature. In our present study, the increase in clearance rates clearly indicates increase in nutritional flow with an increase in temperature.…”
Section: Discussionmentioning
confidence: 90%